Resistance of Aspergillus flavus against Benzoic Acid and SorbicAcid in Chili Paste (Num Prik Ta–Dang) - ทุริสุทธิ์ ยศยา; ทัศนอุดม อรรณพ; วัฒนศิริธรรม ลัดดา; ตุ้ยเต็มวงศ์ ฆรณี; มหากาญจนกุล วราภา (KKU Science Journal, 2016)
Num Prik Ta Dang , a traditional chili paste, is a popular condiment among Thai consumer. This product has a short shelf-life which common preservatives such as benzoate and/or sorbate are added by manufacturers, therefore often found these preservatives exceed the maximum limit according to food regulation. The aim of this study was to investigate the resistance of contaminated mold in Num Prik Ta Dang against benzoic acid and/or sorbic acid in order to recommend the proper use of these preservatives. Survey of 60 samples of Num Prik Ta Dang sold in 20 provinces of Central and Eastern part of Thailand was conducted. Results found that the pH value of chili paste ranged from 4.0–6.35, while aw value was 0.63–0.93. Benzoic acid and sorbic acid were added as 78% and 13%, ranging from 169–5,302 mg/kg and 2– 1,760 mg/kg, respectively. Whereas 23 of 60 samples (40%) contained benzoic exceed the maximum limit (at 1000 mg/kg). High load of yeast and mold (95%, >102 CFU/g) and total bacteria (58%, >105 CFU/g) was found. Moreover pathogenic bacteria such as C. perfringens was found 21.7% (>102 CFU/g). Then Aspergillus flavus 0701, isolated from chili paste, were cultured on Potato Dextrose Agar adjusted pH at 4.5 and 5, and aw at 0.85 and 0.9. Isolate was inhibited by sorbic acid at concentration 800 mg/kg (pH 5.0 or 4.5, aw 0.90). At both level of pH when reduced aw to 0.85, the growth of A. flavus 0701 was inhibited completely by adding benzoic acid at 500 mg/kg. Using of both preservatives to prolong shelf-life of food depends on combination factors of mold strain, aw and pH of food. In this simulated conditions in food model results showed adding only sorbic acid was the best effective against preservative resistant mold, following by the combination of benzoic and sorbic acid, and lastly only benzoic acid added.